ISUOG Practice Guidelines: ultrasound assessment of fetal biometry and growth. (6th June 2019) - Salomon, L.J.; Alfirevic, Z.; Da Silva Costa, F.; Deter, R.L.; Figueras, F.; Ghi, T.; Glanc, P.; Khalil, A.; Lee, W.; Napolitano, R.; Papageorghiou, A.; Sotiriadis, A.; et al.
Abstract : INTRODUCTION: These Guidelines aim to describe appropriate assessment of fetal biometry and diagnosis of fetal growth disorders. These disorders consist mainly of fetal growth restriction (FGR), also referred to as intrauterine growth restriction (IUGR) and often associated with small‐for‐gestational age (SGA), and large‐for‐gestational age (LGA), which may lead to fetal macrosomia; both have been associated with a variety of adverse maternal and perinatal outcomes. Screening for, and adequate management of, fetal growth abnormalities are essential components of antenatal care, and fetal ultrasound plays a key role in assessment of these conditions. The fetal biometric parameters measured most commonly are biparietal diameter (BPD), head circumference (HC), abdominal circumference (AC) and femur diaphysis length (FL). These biometric measurements can be used to estimate fetal weight (EFW) using various different formulae 1 . It is important to differentiate between the concept of fetal size at a given timepoint and fetal growth, the latter being a dynamic process, the assessment of which requires at least two ultrasound scans separated in time. Maternal history and symptoms, amniotic fluid assessment and Doppler velocimetry can provide additional information that may be used to identify fetuses at risk of adverse pregnancy outcome. Accurate estimation of gestational age is a prerequisite for determining whether fetal size is appropriate‐for‐gestational age (AGA). Except for pregnancies arising from assisted reproductive technology, the date of conception cannot be determined precisely. Clinically, most pregnancies are dated by the last menstrual period, though this may sometimes be uncertain or unreliable. Therefore, dating pregnancies by early ultrasound examination at 8–14 weeks, based on measurement of the fetal crown–rump length (CRL), appears to be the most reliable method to establish gestational age. Once the CRL exceeds 84 mm, HC should be used for pregnancy dating 2–4 . HC, with or without FL, can be used for estimation of gestational age from the mid‐trimester if a first‐trimester scan is not available and the menstrual history is unreliable. When the expected delivery date has been established by an accurate early scan, subsequent scans should not be used to recalculate the gestational age 1 . Serial scans can be used to determine if interval growth has been normal. In these Guidelines, we assume that the gestational age is known and has been determined as described above, the pregnancy is singleton and the fetal anatomy is normal. Details of the grades of recommendation used in these Guidelines are given in Appendix 1. Reporting of levels of evidence is not applicable to these Guidelines. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. Abstract : Pautas de ISUOG para la práctica: evaluación ecográfica de la biometría y el crecimiento fetal INTRODUCCIÓN: El objetivo de estas Pautas es describir la evaluación adecuada de la biometría fetal y el diagnóstico de los trastornos del crecimiento fetal. Estos trastornos consisten principalmente en la restricción del crecimiento fetal (RCF), también conocida como restricción del crecimiento intrauterino (RCIU), que a menudo está asociada con un tamaño pequeño para la edad gestacional (PEG) o grande para la edad gestacional (GEG), que pueden dar lugar a la macrosomía fetal; ambos se han asociado con una variedad de resultados maternos y perinatales adversos. La detección y el tratamiento adecuado de las anomalías del crecimiento fetal son componentes esenciales de la atención prenatal, y la ecografía fetal desempeña un papel fundamental en la evaluación de estas afecciones. Los parámetros biométricos fetales medidos con mayor frecuencia son (todas las siglas procedentes del inglés) el diámetro biparietal (BPD), el perímetro cefálico (HC), el perímetro abdominal (AC) y la longitud de la diáfisis del fémur (FL). Estas mediciones biométricas se pueden utilizar para estimar el peso del feto (PEF) mediante fórmulas diferentes 1 . Es importante diferenciar entre el concepto de tamaño fetal en un momento dado y el crecimiento fetal en sí, siendo este último un proceso dinámico cuya evaluación requiere al menos dos ecografías separadas en el tiempo. La historia y los síntomas de la madre, la evaluación del líquido amniótico y la velocimetría Doppler pueden proporcionar información adicional que se puede utilizar para identificar los fetos bajo riesgo de resultados adversos del embarazo. La estimación precisa de la edad gestacional es un prerrequisito para determinar si el tamaño del feto es apropiado para la edad gestacional (AEG). Excepto en el caso de los embarazos procedentes de tecnologías de reproducción asistida, la fecha de concepción no se puede determinar con precisión. Clínicamente, la fecha de la mayoría de los embarazos se establece en función del último período menstrual, aunque a veces esto puede ser incierto o poco fiable. Por lo tanto, el fechado de los embarazos mediante ecografía temprana a las 8‐14 semanas, mediante la medición de la longitud céfalo‐caudal (LCC) fetal, parece ser el método más fiable para establecer la edad gestacional. Una vez que la LCC excede los 84 mm, se debe usar el HC 2–4 para establecer la fecha del embarazo. El HC, con o sin FL, se puede utilizar para estimar la edad gestacional a partir de la mitad del primer trimestre si no se dispone de una ecografía del primer trimestre y el historial menstrual no es fiable. Cuando se ha establecido la fecha prevista del parto mediante una exploración temprana precisa, no se deben utilizar exploraciones posteriores para recalcular la edad gestacional 1 . Las exploraciones en serie se pueden utilizar para determinar si el intervalo del crecimiento ha sido normal. En estas Pautas se asume que la edad gestacional es conocida y ha sido determinada según lo anterior, que el embarazo es de feto único y que la anatomía fetal es normal. En el Apéndice 1 se detallan los grados de recomendación utilizados en estas Pautas. El informe sobre los niveles de evidencia no es aplicable a estas Pautas. 摘要: ISUOG实践指南:胎儿生物测量与生长的超声评估 引言: 本指南旨在描述胎儿生物测量的正确评估及胎儿生长障碍的诊断。这些疾病主要包括又称为宫内生长受限(IUGR)且往往与小于胎龄(SGA)有关的胎儿生长受限(FGR)，以及可能导致胎儿巨大的大于胎龄(LGA)。这两种疾病都与各种孕产期围产期不良结局有关。胎儿生长异常的筛查和适当处理是产前保健的重要组成部分，胎儿超声检测在这些疾病的评估中起着关键作用。最常测量的胎儿生物特征参数有双顶径(BPD)、头围(HC)、腹围(AC)和股骨骨干长度(FL)。可以根据这些生物特征测量值，运用各种不同的公式估算胎儿体重(EFW)。 1 务必要区分给定时间点胎儿大小与胎儿生长这两个不同的概念，后者是一个动态的过程。胎儿生长评估至少需要不同时间点的两次超声波扫描检测。产妇的病史和症状、羊水评估和多普勒测速可以提供更多信息，可以据此识别有不良妊娠结局风险的胎儿。准确估算胎龄是确定胎儿大小是否适合胎龄(AGA)的先决条件。无法精确确定受孕日期，辅助生殖技术引发的妊娠除外。临床上主要将末次月经日期定为受孕日期，虽然有时可能不太确定或不太可靠。因此，根据胎冠臀长(CRL)测量结果和第8‐14周早期超声波检测结果确定受孕日期，似乎是确定胎龄的最可靠方法。如果CRL超过84毫米，就要根据HC来确定受孕日期。 2–4 如果无法进行孕早期扫描且月经史不可靠，就可以通过HC——不管有没有FL——来估算孕中期孕龄。通过准确的孕早期扫描确定预产期后，就不要再做后续扫描来重新估算胎龄了。 1 可以通过连续扫描确定胎儿间隔生长是否正常。在本指南中，我们假设胎龄已知且已通过上述方式确定胎龄，孕产单生儿且胎儿解剖正常。本指南所用的推荐等级详情如附录1所示。本指南不适用报告证据等级。